GAMBARAN PENGETAHUAN DAN SIKAP AKSEPTOR KB DALAM MEMILIH KONTRASEPSI IMPLAN DI PUSKESMAS PEGASING KABUPATEN ACEH TENGAH - maya rahmayani (Jurnal Ilmiah Cerebral Medika, 2020)
The BKKBN's 2020 vision is to become a reliable and trusted institution in realizing abalanced growing population and quality families. And the mission has five values, namely smart, tough, cooperation, integrity and sincere. Contraceptive implants are contraceptives thatareinserted under the skin of the inner upper arm. The purpose of this study was to describe theknowledge and attitudes of family planning acceptors in choosing implant contraceptives at the Pegasing Community Health Center in Central Aceh Regency in 2020. This research is descriptivewith a cross-sectional approach. The sample in this study is all family planning acceptors whovisited the Pegasing Community Health Center during the study. totaled 52 acceptors. The resultsof the study of 52 family planning acceptors were categorized as not choosing implantcontraception, namely 42 people (80.8%), which was influenced by the lack of knowledge of family planning acceptors, namely 32 people (61.1%). And the attitude of negative family planningacceptorsin choosing implant contraception is as many as 31 people (59.6%)